Revisiting the role of the African Commission on Human and Peoples' Rights in eradicating child labour in Africa - Chirwa, Shyreen; Kaime, Thoko (Intractable Problems of Human Rights, 2025)
Child labour remains one of the most persistent human rights challenges in Africa, undermining children’s rights to education, health, and development as enshrined in regional and international human rights instruments. Despite the existence of comprehensive legal frameworks such as the African Charter on the Rights and Welfare of the Child (ACRWC) and the African Charter on Human and Peoples’ Rights (African Charter), millions of children across the continent continue to be subjected to exploitative and hazardous work. This chapter revisits the role of the African Commission on Human and Peoples’ Rights (ACHPR) in eradicating child labour in Africa, assessing its effectiveness, limitations, and potential for transformative impact. It critically analyses the ACHPR’s promotional, protective, and interpretative mandates, focusing on its use of state reporting and concluding observations, special mechanisms and collaborations, and communications procedures, to advance children’s rights. The chapter further explores the synergies between the ACHPR and the African Committee of Experts on the Rights and Welfare of the Child (ACERWC) in addressing systemic violations of children’s rights through joint initiatives and advocacy. The Chapter finds that while the ACHPR has made notable strides in mainstreaming children’s rights into its broader human rights agenda, challenges such as limited enforcement powers, inadequate state compliance, and resource constraints hinder its effectiveness. The chapter concludes that strengthening institutional collaboration, enhancing monitoring mechanisms, and ensuring greater accountability of state parties in addressing root causes are critical to enabling the ACHPR to play a more decisive role in eradicating child labour and upholding children’s rights in Africa.